Substantiating the potential for a new technique (impedance oculopneumoplethysmography) to assist in diagnosing microvascular ciliary body ischemia - Kovalchuk, O.G. (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To provide theoretical substantiation of the potential for a new technique, impedance oculopneumoplethysmography (OPPG), to assist in diagnosing microvascular ciliary body ischemia. Methods: Modeling the distribution of high-frequency current in ocular tissues during ocular rheography; modeling the conversion of the local short-term vacuum compression of the globe to the increase in intraocular pressure (IOP); estimating the height of scleral deflection averaged over the site of local vacuum compression based on the IOP rise. Results: A new method for estimating the state of intraocular circulation, impedance OPPG, was proposed, and its potential to assist in diagnosing microvascular ciliary body ischemia by identifying low (< 35.0 mm Hg) diastolic ocular perfusion pressure (OPP) in the ciliary body metarterioles was theoretically substantiated. The diastolic OPP corresponds to the “local short-term vacuum compression” induced IOP rise at which a decrease in the pulsatile blood volume amplitude is registered by ocular rheography. With this method used as per the utility model (i.e., with a ring-shaped suction cup (RSCP) applied perilimbally, and with rheography electrodes, as per Pat. UA 112192), the diastolic perfusion pressure is estimated only in the arterioles of the ciliary body microcirculation system. Using a mathematical model, a formula K×(VAC/D4) was derived for estimating the increase in IOP based on the vacuum pressure applied, VAC, and globe diameter, D, with the factor K depending on the dimensions of the specific RSCP. Conclusion: The approach proposed for estimating the OPP in the metarterioles may be useful for early diagnosis of impaired vascular microcirculation in eyes with glaucoma (including low-tension glaucoma), myopia, diabetic angiopathy, peripheral retinal degeneration, age-related macular degeneration, or uveitis, and may enable estimating the efficiency of treatment for these disorders after conservative therapy or surgical procedures.